Implementation of Talqin, Tafahhum, Tahfidz, and Murojaah Methods In The Tahfidzul Al-Qur'an Program For The Students of University of Darussalam Gontor For Girls Mantingan, Ngawi, East Java - Astuti Sifa’urahmah; Aulia Indah Zahra Ibrahim (Educan : Jurnal Pendidikan Islam, 2020)
Memorizing Al-Qur'an is a necessity for every Muslim in memorizing letters during the obligatory prayers and sunnah prayers One of the efforts of the Indonesian people is to develop a program of memorizing the Qur'an in formal education including universities. Students are agents of change who are responsible for strengthening society and religion by safeguarding the Qur'an and Sunnah. With the "Al-Qur'an Memorization Program" for students is expected to be able to minimize deficiencies and improve the situation, of course, by implementing this method requires the "method of memorizing the Qur'an" that can achieve indicators and noble goals of learning in an institution. The purpose of this study is to describe: 1) the implementation of the Talqin, Tafahhum, Tikrar, and Murojaah methods in the Tahfidzul Al-Qur'an program at Darussalam University Gontor Putri, Mantingan, Ngawi, East Java 2) supporting factors and the implementation of Talqin, Tafahhum, and supporting methods Tikrar, and Murojaah at the Tahfidzul Al-Qur'an program at Darussalam Gontor Putri University, Mantingan Ngawi, East Java. This research is a descriptive qualitative research. Data collection techniques using several methods, namely: 1) interview method, used to collect new data related to the implementation of the Talqin, Tafahhum, Tikrar, and Murojaah methods in the Tahfidzul Al-Qur'an program at Darussalam Gontor Putri University, 2) observation methods, used to collect data related to the description of facilities and infrastructure supporting the implementation of the Talqin, Tafahhum, Tikrar, and Murojaah methods in the Tahfidzul Al-Qur'an program at Darussalam University of Gontor Putri, 3) documentation method, used to collect data related to documentation of the implementation of the Talqin, Tafahhum, Tikrar, and Murojaah methods in the Tahfidzul Al-Qur'an program at Darussalam University Gontor Putri. And in analyzing data, researchers used an interactive analysis of the Miles and Huberman model with the steps of average reduction, data presentation and conclusion drawing. The majority of female students in the tahfidz program use methods applied by universities such as reciting and understanding, reading Al-Qu'ran to be memorized which is the Talqin and Tafahum methods, after that repeating the memorization more than once is the Takrir method and finally depositing it to muhafidzoh as a form of the Murojaah method.